Budidaya Sayuran Organik dalam Pemanfaatan Perkarangan Rumah Warga Desa Kampung Baru Dusun Pagar Sar - Ruwaidah, Ruwaidah; Megawati, Betti; Nursalimah, Nursalimah; Pohan, Siti Aminah; Harahap, Tati Khofifah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
A house yard is an open area around a residence. Even the smallest home garden can be utilized if it is managed well and will produce high-value vegetables. The problem that occurs today is that people leave empty land without managing it to produce high value. Therefore, to produce high-value vegetables, use limited land by cultivating vegetables using empty land belonging to one of the residents of Kampung Baru Village, Dusun Pagar Sari, this cultivation activity is called organic. As well as land use in organic vegetable farming which is more environmentally friendly. The aim of this article is to help the community's economy and produce a healthy environment by utilizing home gardens. The method used by this service is the method of socialization and planting training using the polybag technique, which includes preparation, implementation, monitoring and evaluation. The results obtained are that rural communities, especially housewives, gain experience and knowledge about organic vegetable cultivation techniques.